2021
DOI: 10.1038/s41523-021-00333-6
|View full text |Cite
|
Sign up to set email alerts
|

High CYP27A1 expression is a biomarker of favorable prognosis in premenopausal patients with estrogen receptor positive primary breast cancer

Abstract: Abstract27-hydroxycholesterol (27HC), synthesized from cholesterol by the enzyme CYP27A1, differentially impacts estrogen receptor positive (ER+) breast cancer (BC) cell growth depending on estrogen levels. This study examined the association between CYP27A1 expression and prognosis in a cohort of 193 premenopausal patients with lymph node-negative primary BC with limited exposure to adjuvant systemic cancer treatments. In multivariable analyses among patients with ER+ tumors, high CYP27A1 protein and mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…3A). As previously reported (40), the analysis of transcriptomic database (TNMplot) showed that CYP27A1 is expressed in breast cancer in paired tumors (n=7569), adjacent normal breast tissues (n=252) and metastasis (n=82), showing a slight decrease between normal and cancer tissues (Fig 3B). The cell lines used in our studies were chosen because they were reported to express CYP27A1 at various mRNA levels (https://www.proteinatlas.org/), and we confirm that at the protein level by western blotting (Fig 3C).…”
Section: Resultssupporting
confidence: 83%
“…3A). As previously reported (40), the analysis of transcriptomic database (TNMplot) showed that CYP27A1 is expressed in breast cancer in paired tumors (n=7569), adjacent normal breast tissues (n=252) and metastasis (n=82), showing a slight decrease between normal and cancer tissues (Fig 3B). The cell lines used in our studies were chosen because they were reported to express CYP27A1 at various mRNA levels (https://www.proteinatlas.org/), and we confirm that at the protein level by western blotting (Fig 3C).…”
Section: Resultssupporting
confidence: 83%
“…We systematically assessed the expression level and clinical significance of CYP27A1 in LUAD. Based on our findings, a poor prognosis for LUAD patients was found to be associated with low expression of CYP27A1, which is consistent with the effect of CYP27A1 on prognosis in breast cancer [ 28 ].…”
Section: Discussionsupporting
confidence: 81%
“…Inhibiting cholesterol conversion to 27-hydroxycholesterol via CYP27A1 has been suggested to prevent breast cancer tumor progression [ 29 ]. However, a study of estrogen receptor positive primary breast cancer showed that high CYP27A1 expression is associated with favorable prognosis [ 30 ]. Studies demonstrated that CYP27A1 deficiency increased the proliferative activity of melanoma cells [ 31 ] and prostate cancer cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%